-
-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathchap-disjoint.tex
155 lines (117 loc) · 4.87 KB
/
chap-disjoint.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
\chapter{Disjoint product}
I remind that
$\coprod X = \bigcup_{i\in\dom X} (i,X_i)$
for every indexed family~$X$ of sets.
\begin{obvious}
$\coprod X\in\mathbf{Set}(\dom X,\im X)$.
\end{obvious}
\begin{defn}
I will call disjoint join of an indexed family~$\mathcal{X}$ of filters the following reloid: $\coprod\mathcal{X} = \bigsqcup_{i\in\dom f}(\{i\}\times^{\mathsf{RLD}}\mathcal{X}_i)$.
\end{defn}
\section{Some funcoids}
\begin{prop}
$\supfun{x\mapsto(i,x)}\mathcal{X}=\{i\}\times^{\mathsf{RLD}}\mathcal{X}$ for every filter~$\mathcal{X}$.
\end{prop}
\begin{proof}
$\supfun{x\mapsto(i,x)}\mathcal{X}=\bigsqcap\setcond{\rsupfun{x\mapsto(i,x)}X}{X\in\up\mathcal{X}}=\bigsqcap\setcond{\{i\}\times X}{X\in\up\mathcal{X}}=\{i\}\times^{\mathsf{RLD}}\mathcal{X}$.
\end{proof}
\begin{prop}
$\supfun{(x\mapsto(i,x))^{-1}}\mathcal{X}=\im(\mathcal{X}|_{\{i\}})$ for a filter~$\mathcal{X}$ on the set $\mathscr{U}\cup\{{\mathscr{U}}\}$ where $\mathscr{U}$~is
a Grothendieck universe.
\end{prop}
\begin{proof}
$\supfun{(x\mapsto(i,x))^{-1}}\mathcal{X}=\bigsqcap\setcond{\rsupfun{(x\mapsto(i,x))^{-1}}X}{X\in\up\mathcal{X}}=\bigsqcap\setcond{\setcond{x}{(i,x)\in X}}{X\in\up\mathcal{X}}=\bigsqcap\setcond{x\in\im X|_{\{i\}}}{X\in\up\mathcal{X}}=\im\bigsqcap\setcond{x\in X|_{\{i\}}}{X\in\up\mathcal{X}}=\im(\mathcal{X}|_{\{i\}})$.
\end{proof}
\section{Cartesian product of funcoids}
\subsection{Definition and basic properties}
\begin{defn}
\emph{Cartesian product} of an indexed family~$f$ of funcoids is
a funcoid \[ \prod^{(J)} f=\bigsqcup_{i\in\dom f}((x\mapsto(i,x))\circ f_i\circ(x\mapsto(i,x)^{-1}). \]
\end{defn}
\begin{prop}
$\supfun{\prod^{(J)}f}\mathcal{X}=\coprod_{i\in\dom f}\supfun{f_i\circ(x\mapsto(i,x)^{-1}}\mathcal{X}$.
\end{prop}
\begin{proof}
\begin{multline*}
\coprod_{i\in\dom f}\supfun{f_i\circ(x\mapsto(i,x)^{-1}}\mathcal{X}=\\
\bigsqcup_{i\in\dom f}(\{i\}\times^{\mathsf{RLD}}\supfun{f_i\circ(x\mapsto(i,x)^{-1}}\mathcal{X})=\\
\bigsqcup_{i\in\dom f}(\supfun{x\mapsto(i,x)}\supfun{f_i\circ(x\mapsto(i,x)^{-1}}\mathcal{X})=\\
\supfun{\prod^{(J)}f}\mathcal{X}.
\end{multline*}
\end{proof}
\subsection{Projections}
\begin{thm}
$f_i$~can be restored from the value of $\prod^{(J)}f=f_i$.
\end{thm}
\begin{proof}
$f_i = (x\mapsto(i,x)^{-1})\circ\prod^{(J)}f\circ(x\mapsto(i,x)^{-1})$
(taken into account that $x\mapsto(i,x)^{-1}$ is a principal funcoid).
\end{proof}
\section{Arrow product of funcoids}
\begin{defn}
\emph{Arrow product} of an indexed family~$f$ of funcoids is
a funcoid \[ \prod^{\rightarrow} f=\bigsqcup_{i\in\dom f}((x\mapsto(i,x))\circ f_i. \]
\end{defn}
\begin{prop}
$\supfun{\prod^{\rightarrow}f}\mathcal{X}=\coprod_{i\in\dom f}\supfun{f_i}\mathcal{X}$.
\end{prop}
\begin{proof}
\begin{multline*}
\coprod_{i\in\dom f}\supfun{f_i}\mathcal{X}=\\
\bigsqcup_{i\in\dom f}(\{i\}\times^{\mathsf{RLD}}\supfun{f_i}\mathcal{X})=\\
\bigsqcup_{i\in\dom f}(\supfun{x\mapsto(i,x)}\supfun{f_i}\mathcal{X})=\\
\supfun{\prod^{\rightarrow}f}\mathcal{X}.
\end{multline*}
\end{proof}
\subsection{Projections}
\begin{defn}
\emph{Arrow projections}
$\pi^{\rightarrow}_i = (x\mapsto(i,x))^{-1}$.
\end{defn}
\begin{thm}
$\pi^{\rightarrow}_i\circ\prod^{\rightarrow}f=f_i$
\end{thm}
\begin{proof}
Because $\pi^{\rightarrow}_i$ is a principal funcoid, we have
\[ \pi^{\rightarrow}_i\circ\prod^{\rightarrow}f=
\bigsqcup_{j\in\dom f}((x\mapsto(i,x))^{-1}\circ(x\mapsto(j,x))\circ f_j). \]
But $(x\mapsto(i,x))^{-1}\circ(x\mapsto(j,x))$ is the idenitity if $i=j$ or
empty otherwise. So
$\pi^{\rightarrow}_i\circ\prod^{\rightarrow}f=f_i$.
\end{proof}
\section{Cartesian product of reloids}
\subsection{Definition and basic properties}
\begin{defn}
\emph{Cartesian product} of an indexed family~$f$ of reloids is
a reloid \[ \prod^{(J)} f=\bigsqcup_{i\in\dom f}((x\mapsto(i,x))\circ f_i\circ(x\mapsto(i,x)^{-1}). \]
\end{defn}
\begin{conjecture}
$\prod^{(J)}(g\circ f)=\prod^{(J)}g\circ\prod^{(J)}f$.
\end{conjecture}
\subsection{Projections}
\begin{thm}
$f_i$~can be restored from the value of $\prod^{(J)}f=f_i$.
\end{thm}
\begin{proof}
$f_i = (x\mapsto(i,x)^{-1})\circ\prod^{(J)}f\circ(x\mapsto(i,x)^{-1})$.
\end{proof}
\section{Arrow product of reloids}
\begin{defn}
\emph{Arrow product} of an indexed family~$f$ of reloids is
a reloid \[ \prod^{\rightarrow} f=\bigsqcup_{i\in\dom f}((x\mapsto(i,x))\circ f_i. \]
\end{defn}
\subsection{Projections}
\begin{defn}
\emph{Arrow projections}
$\pi^{\rightarrow}_i = (x\mapsto(i,x))^{-1}$.
\end{defn}
\begin{prop}
$\pi^{\rightarrow}_i\circ\prod^{\rightarrow}f=f_i$.
\end{prop}
\begin{proof}
Because $x\mapsto(i,x)$ is a pricipal funcoid, we have
$\pi^{\rightarrow}_i\circ\prod^{\rightarrow}f=
\pi^{\rightarrow}_i\circ\bigsqcup_{i\in\dom f}((x\mapsto(i,x))\circ f_i=
\bigsqcup_{j\in\dom f}((x\mapsto(i,x))^{-1}\circ(x\mapsto(j,x))\circ f_i$.
But $(x\mapsto(i,x))^{-1}\circ(x\mapsto(j,x)$ is the identity if $i=j$ or empty otherwise. So $\pi^{\rightarrow}_i\circ\prod^{\rightarrow}f=f_i$.
\end{proof}